GENDER ASPECTS OF RELATIONSHIP IN THE SYSTEM OF MANAGEMENT - T. V. Andrushchenko; O. V. Cherednyk; R. O. Belozorova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The purpose of this paper is the study of gender aspects of management and relationship between management characteristic and style of leadership from gender typing in order to improve management efficiency. Theoretical basis. To understand the influence of gender mechanisms on the organization’s governance system, it turns out that there is a difference in the approach of women and men to management and leadership. The main characteristics of male and female leadership style, features in making management decisions regarding work and career are given. Originality of a paper is the further development in the theory of gender processes with application of interdisciplinary approaches in studying the phenomenon of gender, not from the point of view of the interactions between two large social groups (men and women), but as a social resource of an organization where men and women represent labor potential, rational use of which is the key to successful management in the organization. The social potential of Ukrainian women can become a valuable resource in a country, a region, and any social organization. Conclusions. In modern society, the unique experience of women’s rule is ignored, indicating that they have significant and little used management potential. An analysis of gender interactions in management processes revealed the active desire of women for career growth and success in individual image. However, the transformation of the gender sphere in an organization reflects the preference of patriarchal relations, which is an obstacle to the advancement of women in the managerial structure and, accordingly, requires them to make significant efforts to achieve equal management opportunities with men. To ensure the effectiveness of the organization, it is necessary to take into account the gender factor and comply with gender balance in management positions.